2009
DOI: 10.1016/j.lfs.2009.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity of long-circulating and pH-sensitive liposomes containing cisplatin in mice after intraperitoneal administration

Abstract: These findings reveal that SpHL-CDDP can eliminate CDDP-induced toxicity and is thus a promising candidate for intraperitoneal chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 16 publications
3
26
0
Order By: Relevance
“…In the biodistribution assays, two-way analysis of variance (ANOVA) was used to compare differences between the groups. To analyze the variation in body weight, the value before treatment was used as the covariate, 24 and one-way ANOVA, followed by Bonferroni's post-test, was used to compare differences between the groups. To analyze biochemical parameters, the computed normalized absorbance ratios were used, by correcting the mean optical density value for each sample from NQ, NQC, NQC-AmpB, and free AmpB groups, and dividing it by the mean optical density value from the control group.…”
Section: Discussionmentioning
confidence: 99%
“…In the biodistribution assays, two-way analysis of variance (ANOVA) was used to compare differences between the groups. To analyze the variation in body weight, the value before treatment was used as the covariate, 24 and one-way ANOVA, followed by Bonferroni's post-test, was used to compare differences between the groups. To analyze biochemical parameters, the computed normalized absorbance ratios were used, by correcting the mean optical density value for each sample from NQ, NQC, NQC-AmpB, and free AmpB groups, and dividing it by the mean optical density value from the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, investigations have shown that about 20% of acute renal failure cases among hospitalized patients are due to platinum-based chemotherapy [4,19,22,27]. Several authors agree that renal damage due to cisplatin is irreversible.…”
Section: Discussionmentioning
confidence: 99%
“…The encapsulation of CDDP in liposomes did not affect the size or the zeta potential of the liposomes, as we previously reported. 7,8 The encapsulation percentage of CDDP into liposomes proved to be similar in both SpHL-CDDP and NSpHL-CDDP. All formulations offered an appropriate size and homogeneity for IV administration.…”
Section: Discussionmentioning
confidence: 89%
“…6 The present study's research group has developed longcirculating and pH-sensitive liposomes containing CDDP (SpHL-CDDP) which previously showed both two-and three-fold higher values of median lethal doses than those obtained for free CDDP after their intravenous (IV) and intraperitoneal administration in healthy mice, respectively. 7,8 At the same time, hematological investigations revealed no alteration in red and white blood cell counts upon SpHL-CDDP administration in mice. In addition, SpHL-CDDP treatment caused no pronounced alterations in the blood urea and creatinine levels, nor did it induce morphological alterations in the kidneys of the mice.…”
Section: Introductionmentioning
confidence: 87%